Factors Associated with Hand Washing Practices among Secondary School Students in Ndorwa East Constituency in Kabale District - Benja, Twinomuhwezi; Topher, Byamukama; Nathan, Nshakira (Texila International Journal of Public Health, 2022)
Despite the worldwide Global Hand Washing Day campaign, which targets school children as the most effective agents for behaviour change, there is limited documentation in various school settings. The purpose of the study was to assess the factors associated with hand washing practices among secondary school students in Ndorwa East Constituency in the Kabale district. The study used both quantitative and qualitative methods to collect data from a sample of 291 students from five schools. Results: Of the 291 respondents enrolled, 219(77%) washed their hands after the rest room. Factors associated with a higher likelihood of hand washing practice among secondary school students in Ndorwa East Constituency–Kabale District were being aged <18 years (aOR =8.1, 95%CI: 2.65-21.61, p<0.001), presence of water for hand washing (aOR =50.7,95%CI:11.50-309.38,p<0.001), presence of hand washing stations (aOR=7.3,95%CI:2.72-30.37, p<0.001), and cleanliness of hand washing stations (aOR=70.0,95%CI:10.44-605.6, p<0.001). The factors associated with hand washing practices were presence of water for hand washing, the presence of hand washing stations in schools, cleanliness of hand washing stations. The study suggests that the school administrators should sensitize all students to continue practicing washing hands. This would help in preventing students from diseases associated with poor hand hygiene practices.